The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/abd1806-4841.20132219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiological profile of vitiligo in children and adolescents

Abstract: 94 children and 25 adolescents, 42% male and 58% female, aged predominantly between six and ten years old (40%) were studied at the Martagão Gesteira Childcare and Pediatrics Institute (Rio de Janeiro Federal University) between 2005 and 2011. The prevalent clinical form of vitiligo was the generalized type (34%). Although the clinical response was similar between the treatment modalities, we decided for low and high power topical steroids in our routine. Halo nevi were found in seven (5.9%) cases. Thirty (25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 7 publications
4
27
0
3
Order By: Relevance
“…15 Onset before age 2 years represents 11% of pediatric-onset cases, 28% of cases start between 2 and 5 years, 40% of cases begin between 5 and 10 years, and 21% between 10 and 18 years, demonstrating that median age of onset is between 5 and 10 years of age. 16 In a cohort of Indian children, 56.7% of pediatric cases were noted in childhood between 8 and 12 years. 17 Early-onset disease (before age 12 years) represented 35.2% of cases in an Indian cohort.…”
Section: Epidemiology Of Pediatric Vitiligomentioning
confidence: 99%
See 1 more Smart Citation
“…15 Onset before age 2 years represents 11% of pediatric-onset cases, 28% of cases start between 2 and 5 years, 40% of cases begin between 5 and 10 years, and 21% between 10 and 18 years, demonstrating that median age of onset is between 5 and 10 years of age. 16 In a cohort of Indian children, 56.7% of pediatric cases were noted in childhood between 8 and 12 years. 17 Early-onset disease (before age 12 years) represented 35.2% of cases in an Indian cohort.…”
Section: Epidemiology Of Pediatric Vitiligomentioning
confidence: 99%
“…Of the 25% of children with vitiligo evaluated for psychological issues, 60% reported psychological problems in a cohort of 119 Brazilian children. 16 A recent review article of quality-of-life issues in childhood skin disease stated: "In general, patients with vitiligo experience low self-esteem, social stigmatization, shame, avoidance of intimacy, anxiety, depression, adjustment disorder, fear, suicidal ideation, and other psychiatric morbidity." 47 Recent studies have suggested that childhood vitiligo impacts quality of life similarly to psoriasis, as children enter adulthood.…”
Section: The Psychological Impact Of Vitiligomentioning
confidence: 99%
“…It is the result of a loss of functioning of the melanocytes (4) due to destruction of or damage to these cells, resulting in decreased or absent pigmentation of the skin, hair, and mucous membranes (5)(6)(7). The pathogenetic mechanism of vitiligo is unknown (8).…”
mentioning
confidence: 99%
“…Despite being the are similar for 0-5 and 6-10 years old, but those for the 12-18 year olds are different. While some authors report that the majority of their cases is aged between 6-12, 53.38% of the cases in our study was aged between 12-18 (18). The reason could be delayed arrival of the patients to us.…”
Section: Discussionmentioning
confidence: 60%
“…The most frequent non-segmental type vitiligo observed in children is generalized (78%), followed by focal vitiligo (1). Focal vitiligo is seen in around 14-29 % of the cases (18). Some authors have reported that in children vitiligo is mostly located around the eye and neck, followed by lower extremity, torso, upper extremity and perianal are (15).…”
Section: Discussionmentioning
confidence: 99%